Gender differences in risk aversion and patience: Evidence from a representative survey - Dániel Horn; Hubert János Kiss (Hungarian Academy of Sciences, Institute of Economics, 2019)
We measure risk aversion and patience in a non-incentivized way using a representative sample of the Hungarian adult population. We elicit risk aversion with a task similar to Gneezy and Potters (1997)'s investment game and find that females risk about 8.5 % less than males when we do not consider any additional controls. However, even when we add extensive controls (related to demography, region, family, education, employment, income and wealth) the difference decreases only slightly and remains significant at conventional levels. We carry out the same exercise for patience and document no significant gender differences in any specification.
Keywords: D8; J16; 330; gender differences; patience; representative survey; risk attitude